Antarctic intertidal macroalgae under predicted increased temperatures mediated by global climate change: Would they cope? - Celis-Pla, Paula S. M.; Moenne, Fabiola; Rodriguez-Rojas, Fernanda; Pardo, Diego; Lavergne, Celine; Moenne, Alejandra; Brown, Murray T.; Huovinen, Pirjo; Gomez, Ivan; Navarro Martinez, Nelso Patricio; Saez, Claudio A. (My University, 2020)
The Antarctic Peninsula is one of the regions to be most affected by increase in sea surface temperatures (SSTs) mediated by Global Climate Change; indeed, most negative predictions imply an up to 6 degrees C increment by the end of the XXI century. Temperature is one of the most important factors mediating diversity and distribution of macroalgae, although there is still no consensus as to the likely effects of higher SSTs, especially for polar seaweeds. Some available information suggests that potential strategies to withstand future increases in SSTs will be founded upon the glutathione-ascorbate cycle and the induction of chaperone-functioning heat shock proteins (HSPs); however, their eventual role, even for general stress responses, is unclear. The intertidal green, brown and red macroalgae species Monostroma hariotii, Adenocystis utricularis and Pyropia endiviifolia, respectively, from King George Island, Antarctic Peninsula, were exposed to 2 degrees C (control) and 8 degrees C (climate change scenario) for up to 5 days (d). Photosynthetic activity (alpha(ETR) and ETRmax and Ek(ETR)), photoinhibition (F-v/F-m) and photoprotection processes (alpha(NPQ), NPQ(max) and Ek(NPQ)) provided no evidence of negative ecophysiological effects. There were moderate increases in H2O2 production and levels of lipid peroxidation with temperature, results supported by stable levels of total glutathione and ascorbate pools, with mostly higher levels of reduced ascorbate and glutathione than oxidized forms in all species. Transcripts of P. endivdfolia indicated a general upregulation of all antioxidant enzymes and HSPs genes studied under warmer temperature, although with different levels of activation with time. This pioneering investigation exploring different levels of biological organization, suggested that Antarctic intertidal macroalgae may be able to withstand future rise in SSTs, probably slightly altering their latitudinal distribution and/or range of thermal tolerance, by exhibiting robust glutathione-ascorbate production and recycling, as well as the induction of associated antioxidant enzymatic machinery and the syntheses of HSPs. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: rhodophyceae; ulvophyceae; phaeophyceae; global warming; extremophiles